Implementation of Universal Awareness in Management of Hospital Environment as A Business for Prevention of Nosocomial Infections in Pariaman Regional General Hospital - Aulia Asman; Siti Fatimah (Science and Environmental Journal for Postgraduate, 2020)
The high prevalence of nosocomial infections in hospitals with infectious diseases such as HIV / AIDS, hepatitis B virus and pulmonary tuberculosis and other infectious diseases means that the risk of health workers who can be infected with infectious diseases, especially if vigilance against blood and bodily fluids is not carried out against all patients. The purpose of this study was to see a picture of the implementation of universal vigilance in nurses at Pariaman District Hospital. Preliminary survey conducted by researchers at Pariaman District Hospital of 8 nurses, some actions of officers who have the potential to increase transmission of disease to themselves, patients served and the wider community, namely improper hand washing, where 2 nurses were seen only washing their hands with use water the gloves were not quite right, after researchers saw that 1 piece of gloves was found to be torn. Descriptive research method. The study was conducted at Pariaman District Hospital. The population in the study was all nurses in the inpatient room of Pariaman District Hospital, amounting to 77 people. The sampling technique is total sampling. Data processing is done univariately. Based on the results of the study, it was found that 46.8% took actions to wash hands improperly, 54.5% took measures to use protective equipment that were less appropriate, 32.5% took actions to administer the syringe less precisely. It is expected that nurses must maintain the health and safety of themselves and clients and be responsible as executors and need to apply work procedures, universal precautions and adhere to them in carrying out daily nursing actions.